Hybrid Photovoltaics cell with triboelectric nanogenerator: Overcoming energy availability limits and reducing optical scattering losses - Sivasubramanian, Ramsundar; Vaithilingam, Chockalingam Aravind; Paiman, Suriati; Sharma, Ashish; V, Indragandhi (John Wiley and Sons, 2025)
Solar photovoltaics has long been a major research area in renewable and sustainable energy, with a large percentage of these efforts directed towards resolving PV limitations, the most critical of which is energy availability. The amount of solar PV power output is related to the amount of irradiation incident on it; hence, times of no or low irradiation levels result in zero or reduced power generation. The design and analysis of the optical performance of a contact-separation triboelectric nanogenerator integrated hybrid PV cell that can scavenge energy from rain without interfering with the device's normal operation is presented in this work. The hybrid cell's redesigned materials and structure enable it to minimize optical scattering losses recorded at the top glass layer of conventional PV devices by up to 50% while enhancing transmittivity from 90% to 95% across the visible wavelength range of 400–800 nm.